ANALISIS LABA USAHA TERNAK SAPI DI KABUPATEN SIMALUNGUN - Fathimah, Vidya; Bintang Romauli (Universitas Haji Sumatera Utara, 2025)
The purpose of this study was to determine the profit from cattle sales in Simalungun Regency, especially in the villages of Kampung Petani and Tanjung Marihat. In Simalungun Regency, especially in the villages of Kampung Petani and Tanjung Marihat, it is one of the potential cattle farming businesses for buying and selling cattle. This research method uses quantitative descriptive analysis, survey method (case study). Data collection techniques use observation, interviews and documentation. The results of the study show a comparison of cattle sales profits between the villages of Kampung Petani and Tanjung Marihat from 2021 to 2023, which always experiences profits every year, namely Kampung Petani Village. In 2021, Kampung Petani Village made a profit of IDR 259,714,500, in 2022 it made a profit of IDR 28,714,500, and in 2023 it made a profit of IDR 78,714,500. While Tanjung Marihat Village in 2021 made a profit of IDR. 222,835,000, in 2022 experienced a loss of IDR. 67,165,000, and in 2023 experienced a loss of IDR. 117,165,000. It can be analyzed that the village with the best sales is Kampung Petani Village. Keywords: Profit; Cattle Farming; Business.